Revealing the Atomic Defects of WS2 Governing Its Distinct Optical Emissions - Lin, Yung‐Chang; Li, Shisheng; Komsa, Hannu‐Pekka; Chang, Li‐Jen; Krasheninnikov, Arkady V.; Eda, Goki; Suenaga, Kazu (Advanced functional materials, 2018)
Defects and their spatial distribution are crucial factors in controlling the electronic and optical properties of semiconductors. By using scanning transmission electron microscopy and electron energy loss spectroscopy, the type of impurities/defects in WS2 subdomains with different optical properties is successfully assigned. A higher population of Cr impurities is found in the W‐terminated edge domain, while the S‐terminated domain contains more Fe impurities, in accordance with the luminescence characteristics of chemical‐vapor‐grown WS2 of a hexagonal shape. In agreement with the first‐principles calculations, the domains with Cr substitutional dopants exhibit strong trion emission. Fe atoms tend to gather into trimer configuration and introduce deep acceptor levels which compensate the n‐type doping and suppress trion emission. It is also discovered that the domain with higher luminescence but smaller defect concentration tends to get oxidized more rapidly and degrade the 2D structure with many triangular holes. Excitons tend to accumulate at the edges of the oxidized triangular holes and results in enhanced PL emission. The findings indicate that choosing stable elements as dopant and controlling the number of specific edge structures within a crystal domain of 2D transitional metal dichalcogenides can be a new route to improve the optical properties of these materials. The photoluminescence property of WS2 is strongly influenced by impurities and defects. Higher emission domain contains a higher population of Cr impurities, while the weaker emission domain contains more Fe impurities. Oxidation‐induced void formations with S‐terminated edges tend to enhance the PL emission.